The HF field pattern in the magnetized plasma cylinder of finfte lenght - Grekov, D.L.; Azarenkov, N.A.; Bizyukov, A.A.; Olefir, V.P. (Вопросы атомной науки и техники, 2003)
The PR-1 device is the wide-aperture source of homogeneous plasma. It is using for plasma processing of big diameter samples such as parts of HF antenna and elements of vessel of fusion devices. The paper presented deals with investigation of HF field pattern of the operation regime with external magnetic field. It is shown that the HF fields penetrate into the plasma volume better as compared with the case when magnetic field is turned off. So the plasma flow of greater density could be generated.